Streamflow-Metal Relationship in a Highly Urbanized River Basin: The Blackstone River, Massachusetts, USA - GOKSEL OZDILEK, HASAN; P. MATHISEN, PAUL (Asian Journal of Chemistry, 2010)
Although many water contaminants can be found in urban runoff, certain pollutants depending on site specific characteristics can be used as representative indicators. In this study, copper and lead were taken into account as metal contaminants. The Blackstone River, an interstate river with 74 km length, was examined. Total lead concentration and both lead and copper loads in the river were found to be a function of flow rate. Lead concentration and load is highly depended upon streamflow than that of copper concentration. Furthermore, wet weather was found to be the main responsible factor of increasing total metal concentrations and loads in the river.